1989
DOI: 10.1016/1010-7940(89)90049-3
|View full text |Cite
|
Sign up to set email alerts
|

Early surgical results in the treatment of endomyocardial fibrosis A brazilian cooperative study

Abstract: This report summarizes the surgical experience and early results obtained at four surgical centers in the northeast and south of Brazil. From December 1977 to September 1986, 95 operations were performed on 93 patients, ages 11-59. Bilateral lesions occurred in 42 patients, right lesions in 39, and left lesions in 12. Ventricular decortication and removal of thrombi were performed in all. In right-sided lesions, the tricuspid valve was substituted by a bioprosthesis in 34 cases, and substituted by a tilting di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Early and late results of surgical treatment are well described. [16][17][18][19][20][21] The high operative mortality, of up to one-fifth, observed in most of the reported series indicates the severity of the cardiac cachexia of most patients at the time of operation. It seems to be worse in children who, as shown by our experience, have always presented in the final stage of heart failure and in poor preoperative general condition.…”
Section: Discussionmentioning
confidence: 99%
“…Early and late results of surgical treatment are well described. [16][17][18][19][20][21] The high operative mortality, of up to one-fifth, observed in most of the reported series indicates the severity of the cardiac cachexia of most patients at the time of operation. It seems to be worse in children who, as shown by our experience, have always presented in the final stage of heart failure and in poor preoperative general condition.…”
Section: Discussionmentioning
confidence: 99%
“…EMF extended most frequently to all the endocardium, sticking the chordaes, the papillary muscles and the valvular tissues; what justifies the predominance of valvular replacement rather than valve repair in our study. Hospital mortality was high in the literature: 20% for Moraes (60)(61)(62), 16% for Metras (63); in our study on bilateral EMF in children we reported an early mortality after surgery at 29.4% (64). Fibrosis is not recurring as evocated by Tharakan (59); it indicates the end of a pathological process and the proof was given during an autopsy carried out in Abidjan with a patient 4 years after a right EMF surgery (65).…”
Section: Emfmentioning
confidence: 99%
“…73 Since most patients have extensive disease at the time of presentation; therefore, survival after diagnosis is relatively brief, averaging approximately two years after symptom onset. 74 In one study, 95% of a group of patients had died at two years. 75 In a second study, 44% of patients died within one year after the onset of symptoms, and another 40% of patients died 1-3 years after onset of symptoms.…”
Section: Prognosismentioning
confidence: 99%